(untitled) (The Review of Diabetic Studies, 2024)
Alzheimer’s disease (AD) is a chronic and progressive neurodegenerative disorder characterized by extracellular amyloid-β (Aβ) plaque deposition and intracellular neurofibrillary tangles formed by hyperphosphorylated tau protein. These pathological hallmarks drive synaptic dysfunction, neuroinflammation, neuronal loss, and cognitive decline. Current pharmacological therapies primarily provide symptomatic benefit and fail to modify the underlying disease process, highlighting the urgent need for disease-modifying anti-Alzheimer’s disease (DMAD) strategies. Therapeutic approaches aimed at inhibiting the aggregation of Aβ and tau or enhancing their clearance remain the most validated disease-targeted interventions. Despite decades of research, small-molecule agents have demonstrated limited clinical efficacy in addressing these complex pathological mechanisms. In contrast, the approval of aducanumab, an amyloid-β–targeting monoclonal antibody, has transformed the therapeutic landscape by establishing biological macromolecules as viable DMAD candidates. This milestone has accelerated pharmacological research into nucleic acid- and peptide-based therapeutics, including microRNAs, small interfering RNAs, antisense oligonucleotides, aptamers, and antibodies, which offer enhanced target specificity and mechanistic precision.